(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To determine the efficacy, side effect and acceptability of medical abortion using mifepristone 200mg orally and misoprostol 800?g vaginally in patients less than 49 days of gestation. Materials and methods: Seventy six women who requested termination of pregnancy up to 49 days of gestation were administered 200mg mifepristone orally followed 48 hours later by 800?g of misoprostol per vaginally. Results: Ninty six percent (96%) women had complete abortion with this regimen. There was no ongoing pregnancy. The average duration of per vaginal bleeding was 12-13 days. There were some side effects, which include abdominal pain, vomiting, fever etc. Conclusion: This mifepristone-misoprostol regimen is highly effective in terminating pregnancy in women up to 49 days duration with minimum side effects and this medical method may be advisable to practice as an alternative to surgical procedure where adequate skilled attendance is lacking. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 44-49